Selective and scalable synthesis of sugar alcohols by homogeneous asymmetric hydrogenation of unprotected ketoses - Tindall, Daniel James; Mader, Steffen; Kindler, Alois; Rominger, Frank; Hashmi, A. Stephen K.; Schaub, Thomas (Angewandte Chemie. International edition, 2021)
Sugar alcohols are of great importance for the food industry and are promising building blocks for bio-based polymers. Industrially, they are produced by heterogeneous hydrogenation of sugars with H2, usually with none to low stereoselectivities. Now, we present a homogeneous system based on commercially available components, which not only increases the overall yield, but also allows a wide range of unprotected ketoses to be diastereoselectively hydrogenated. Furthermore, the system is reliable on a multi-gram scale allowing sugar alcohols to be isolated in large quantities at high atom economy.